The future of management - Hamel, Gary (Harvard Business School Press, 2007)
Though this authoritative examination of today's static corporate management systems reads like a business school treatise, it isn't the same-old thing. Hamel, a well-known business thinker and author (Leading the Revolution), advocates that dogma be rooted out and a new future be imagined and invented. To aid managers and leaders on this mission, Hamel offers case studies and measured analysis of management innovators like Google and W.L. Gore (makers of Gore-Tex), then lists lessons that can be drawn from them. He doesn't gloss over how difficult it will be to reinvent management, comparing the new and needed shift in thinking to Darwin's abandoning creationist traditions and physicists who had to look beyond Newton's clockwork laws to discover quantum mechanics. But the steps needed to make such a profound shift aren't clearly outlined here either. The book serves primarily as an invitation to shed age-old systems and processes and think differently.